Imported and intensive care unit-born Acinetobacter baumannii clonal complexes: one-year prospective cohort study in intensive care patients - Martins, Natacha (2013)
Juliana Arruda de Matos. Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta a informação no documento.